Pemberdayaan Masyarakat dalam Produksi Pasir Zeolit Alam di BUMDes Hargomulyo Gunung Kidul - Suharto, Totok Eka; Satar, Ibdal; Permadi, Adi; Hapsari, Wahyu Dewi; Syamsuddin, Arief (Abdimas Indonesian Journal, 2024)
This community service activity is in partnership with the Hargomulyo District/Village Owned Enterprise (BUMDes).. The problems being addressed include the unavailability of natural zeolite rock crushing machine equipment to produce zeolite sand. This activity aims to provide a small-capacity natural zeolite rock crushing machine and train machine operations to produce zeolite sand. Considering the expensive new machines and limited funds, procuring rock crushing machines was carried out by upgrading used rock crushing machines in a workshop. The crushing machine has a chopper, a driving motor powered by a generator, and a sieve for the crushed rock with three-grain sizes. Operational trials of the rock chopping machine show that the machine can produce natural zeolite sand with three-grain sizes. Furthermore, operational training on natural zeolite crushing machines was carried out, which was attended by 20 participants from the Hargomulyo community. This training can increase the empowerment of training participants. The observations during the training showed that 90% of participants could operate a rock-crushing machine to produce natural zeolite sand.